The Use of Integrated Agriculture to Improve Quality of Life of Farmers In Ban Na Sub-district, Nakhon Nayok Province, Thailand (Journal of Namibian Studies : History Politics Culture, 2024)
The objectives of this research were; 1) to study agriculture problems of farmers , 2) to survey the quality of life, 3) to develop model utilizing integrated agriculture to improve life quality of  farmers, and 4) to drive the model to  improve quality of life of farmers in Banna sub-district,  Nakorn Na Yok province, Thailand. This research employs mixed research approaches. The population consists of farmers residing in Banna sub-district, Nakhon Nayok province. The samples include farmers from 237 households. Gathering data via interviews and focused group discussion, the key informants include agricultural officers and 14 village leaders. Questionnaires are utilized to gather data, which is subsequently examined using statistical measures: percentages, averages, and standard deviations. The results revealed that: 1) The challenges faced by farmers in Banna sub-district in the field of agriculture encompass inadequate water resources, soil degradation, chemical usage, and elevated agricultural expenses. 2)  Prior to the implementation of the life quality development model, the quality of life of farmers in Banna subdistrict was at average level. 3) Models aimed at improving quality of life prioritize the enhancement of the economy, mental well-being, physical health, and society. 4) The application of the life quality development model through integrated agriculture in Banna sub-district has resulted in improvements in four dimensions of life quality: economic, mindset, health, and society.